PENYULUHAN DAN PELATIHAN PEMBUATAN ASAP CAIR - Dwi Indah; Roger R Tabalessy; Melisa CH Masengi; Melani Manurung; Hasri Rikola (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Dedication to the community to provide counseling and training on the manufacture of liquid smoke to all types of Micro, Small and Medium Enterprises (UMKM) that produce processed marine products, such as smoked fish in Sorong City. Most UMKM in Sorong City still use traditional food processing methods and simple packaging. Liquid smoke can be used as an alternative in processing smoked fish. In addition, to increase the scale of production, food processors can utilize vacuum packaging technology to extend the shelf life of food products. Community service programs and counseling sessions are expected to increase knowledge and awareness of food processors regarding these alternative technologies. Program participants welcomed this activity and showed interest in starting to use the suggested alternative technology.